MANAJEMEN STRATEGIK DI LEMBAGA PENDIDIKAN ISLAM : INTEGRASI NILAI-NILAI KEISLAMAN DAN PRAKTIK ORGANISASI MODERN - Holidi, Moh.; Ihza Saputra, Yusril; Kamil, Moh.; Thoiful Abrar, Muhammad; Kholilurrohman, Muhammad; Muhlas, Moh.; Mudarris, Badrul (As-Sulthan Journal of Education, 2025)
This study aims to analyze the implementation of strategic management in Islamic educational institutions through the integration of Islamic values ​​with modern organizational practices. The main focus is to understand how Islamic principles such as amanah (trust), ihsan (goodness), and musyawarah (deliberation) can be harmonized with contemporary management approaches that emphasize efficiency, innovation, and accountability. The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, participant observation, and documentation studies in several Islamic educational institutions. The results show that the integration of Islamic values ​​​​into modern organizational practices can strengthen an ethical work culture, increase employee commitment, and encourage the effectiveness of institutional strategies. The implementation of strategic management based on Islamic values ​​​​also produces a balance between spiritual and professional orientations, which has a positive impact on the reputation and competitiveness of the institution. The implications of this study show the importance of formulating strategic management policies that are not only oriented towards material results, but also on strengthening moral and spiritual values ​​​​as the basis for the sustainability of Islamic educational institutions in the modern era.